Spatial distribution and risk assessment of heavy metals in seawater and sediments in Jieshi Bay, Shanwei, China - Zhou, Wen; Cao, Qian; Hong, Man; Lei, Yutao; Wen, Ding; Zhang, Dengfeng (Frontiers in Marine Science, 2022)
The contamination of heavy metals due to human activities has attracted great attention and may lead to serious environmental problems. This research was performed on seawater, sediments, and organisms in Jieshi Bay, China. The level of Cu, Pb, Zn, Cd, Hg, and As, respectively, was measured in each environment to acquire a comprehensive understanding of their sources and distribution and to accomplish a risk assessment. The results showed that the concentration of heavy metals in autumn was higher than those in spring, and surface water has a higher heavy metal content than bottom water. The main sources of these heavy metals could be surface runoff and industrial wastewater discharge in the said bay. Hg was the main pollutant in the seawater. Hg, Cu, Zn, and Cd could easily accumulate in organisms than other heavy metal contents. In addition, even though the concentration of Pb did not exceed the Seawater Quality Standard, decision-makers should still be attentive to the Pb content in fish because of bioaccumulation from seafood product consumption.